Size matters: Grey matter brain reserve predicts executive functioning in the elderly. (October 2018) - Laubach, M.; Lammers, F.; Zacharias, N.; Feinkohl, I.; Pischon, T.; Borchers, F.; Slooter, A.J.C.; Kühn, S.; Spies, C.; Winterer, G.; ,
Abstract: Preserved executive functioning (EF) is crucial for daily functioning in the elderly and it appears to predict dementia development. We sought to clarify the role of atrophy-corrected cortical grey matter (GM) volume as a potential brain reserve (BR) marker for EF in the elderly. In total, 206 pre-surgical subjects (72.50 ± 4.95 years; mean MMSE score 28.50) were investigated. EF was primarily assessed using the Trail Making Test B (TMT B). Global/ lobar GM volumes were acquired with T1 MP-RAGE. Adjusting for key covariates including a brain atrophy index (i.e. brain parenchymal fraction), multiple linear regression analysis was used to study associations of GM volumes and TMT B. All GM volumes - most notably of global GM - were significantly associated with TMT B independently of GM atrophy (ß = −0.201 to −0.275, p = 0.001–0.012). Using atrophy-corrected GM volume as an estimate of maximal GM size in youth may serve as a BR predictor for cognitive decline in future studies investigating BR in the elderly. Highlights: Executive function is a marker for prediction of cognitive decline in the elderly. Atrophy-corrected global grey matter volume predicts EF in the non-demented elderly. Atrophy-corrected global GM volume is a potential quantitative brain reserve marker.